Neotropical ornithology: Reckoning with historical assumptions, removing systemic barriers, and reimagining the future - Soares, Leticia; Cockle, Kristina L.; Ruelas Inzunza, Ernesto; Ibarra, Jose Tomas; Mino, Carolina Isabel; Zuluaga, Santiago; Bonaccorso, Elisa; Rios-Orjuela, Juan Camilo; Montano-Centellas, Flavia A.; Freile, Juan F.; Echeverry-Galvis, Maria A.; Bonaparte, Eugenia Bianca; et al. (My University, 2023)
Lay Summary center dot Research conducted by ornithologists living and working in Latin America and the Caribbean has been historically and systemically excluded from global scientific paradigms, ultimately holding back ornithology as a discipline. center dot To avoid replicating systems of exclusion in ornithology, authors, editors, reviewers, journals, scientific societies, and research institutions need to interrupt long-held assumptions, improve research practices, and change policies around funding and publication. center dot To advance Neotropical ornithology and conserve birds across the Americas, institutions should invest directly in basic field biology research, reward collective leadership, and strengthen funding and professional development opportunities for people affected by current research policies. A major barrier to advancing ornithology is the systemic exclusion of professionals from the Global South. A recent special feature, Advances in Neotropical Ornithology, and a shortfalls analysis therein, unintentionally followed a long-standing pattern of highlighting individuals, knowledge, and views from the Global North, while largely omitting the perspectives of people based within the Neotropics. Here, we review current strengths and opportunities in the practice of Neotropical ornithology. Further, we discuss problems with assessing the state of Neotropical ornithology through a northern lens, including discovery narratives, incomplete (and biased) understanding of history and advances, and the promotion of agendas that, while currently popular in the north, may not fit the needs and realities of Neotropical research. We argue that future advances in Neotropical ornithology will critically depend on identifying and addressing the systemic barriers that hold back ornithologists who live and work in the Neotropics: unreliable and limited funding, exclusion from international research leadership, restricted dissemination of knowledge (e.g., through language hegemony and citation bias), and logistical barriers. Moving forward, we must examine and acknowledge the colonial roots of our discipline, and explicitly promote anti-colonial agendas for research, training, and conservation. We invite our colleagues within and beyond the Neotropics to join us in creating new models of governance that establish research priorities with vigorous participation of ornithologists and communities within the Neotropical region. To include a diversity of perspectives, we must systemically address discrimination and bias rooted in the socioeconomic class system, anti-Blackness, anti-Brownness, anti-Indigeneity, misogyny, homophobia, tokenism, and ableism. Instead of seeking individual excellence and rewarding top-down leadership, institutions in the North and South can promote collective leadership. In adopting these approaches, we, ornithologists, will join a community of researchers across academia building new paradigms that can reconcile our relationships and transform science. Spanish and Portuguese translations are available in the .
Keywords: discovery narrative; discrimination; knowledge construction; north-south relations; parachute science; regional priorities; research agenda